Laboratorios de medios al servicio de la formación en Periodismo - Forero Arango, Ximena; Arias Hidalgo, Walter (Folios, revista de la Facultad de Comunicaciones y Filología, 2024)
This text is derived from an inves tigation that aimed to identify the challenges, actions and work routes to consolidate the De la Urbe media laboratory as a space for exper imentation and innovation, at the service of the undergraduate degree in Journalism at the University of Antioquia. It was carried out from the constructivist paradigm, qualitative, with de scriptive scope, through design-based research. In one of the iterations, coordinators of university journalism laboratories were interviewed. The results indicate that university journalism labora tories are essential today due to the challenges imposed by technological transformation for teaching and learning processes. Being open, welcoming, creative, digital and experimental are some of the conclusions drawn by this investi gation, within the framework of an environment characterized by speed and complexity.